Exhausted ecologies : modernism and environmental recovery - Kalaidjian, Andrew (Cambridge University Press, 2019)
"Surveying the state of literature in the 1930s, E. M. Forster is nostalgic for the relative peace of the Edwardian England of his youth. He paints a picture of the modern world as one without rest, fixity, or security. This characterization of modernity is a common one. Always on the move, ever-expanding, always innovating, the modernist knows no bounds. Forster admits that restlessness gives the modern era its identity, but he frankly finds such a world exhausting"-- Provided by publisher.
Keywords: Modernism (Literature); English literature -- 20th century -- History and criticism.; American literature -- 20th century -- History and criticism.; Civilization, Modern, in literature.; Environment in literature.; Ecocriticism.; Modernisme (Littérature); Littérature anglaise -- 20e siècle -- Histoire et critique.; Littérature américaine -- 20e siècle -- Histoire et critique.; Écocritique.; American literature; Civilization, Modern, in literature; Ecocriticism; English literature; 1900-1999; Criticism, interpretation, etc.